Genome and transcriptome of Papaver somniferum Chinese landrace CHM indicates that massive genome expansion contributes to high benzylisoquinoline alkaloid biosynthesis. (1st January 2021) - Pei, Li; Wang, Baishi; Ye, Jian; Hu, Xiaodi; Fu, Lihong; Li, Kui; Ni, Zhiyu; Wang, Zhenlong; Wei, Yujie; Shi, Luye; Zhang, Ying; Bai, Xue; et al.
Abstract: Opium poppy ( Papaver somniferum ) is a source of morphine, codeine, and semisynthetic derivatives, including oxycodone and naltrexone. Here, we report the de novo assembly and genomic analysis of P. somniferum traditional landrace 'Chinese Herbal Medicine'. Variations between the 2.62 Gb CHM genome and that of the previously sequenced high noscapine 1 (HN1) variety were also explored. Among 79, 668 protein-coding genes, we functionally annotated 88.9%, compared to 68.8% reported in the HN1 genome. Gene family and 4DTv comparative analyses with three other Papaveraceae species revealed that opium poppy underwent two whole-genome duplication (WGD) events. The first of these, in ancestral Ranunculales, expanded gene families related to characteristic secondary metabolite production and disease resistance. The more recent species-specific WGD mediated by transposable elements resulted in massive genome expansion. Genes carrying structural variations and large-effect variants associated with agronomically different phenotypes between CHM and HN1 that were identified through our transcriptomic comparison of multiple organs and developmental stages can enable the development of new varieties. These genomic and transcriptomic analyses will provide a valuable resource that informs future basic and agricultural studies of the opium poppy.